Literasi Berinvestasi di Pasar Modal dengan Focus Group Discussion Kelas Trading - Oki Astarini, Dewa Ayu; Murapi, Ikang; Khairunnisa; Sriwinarti, Ni Ketut; Khairil, Fahrurrohmi (Insan Kreasi Media, 2024)
Financial literacy is a long-term investment that is useful in managing finances effectively. Financial literacy is the key to managing finances wisely. PT. Infinity General Consulting as a consulting company operating in various financial fields certainly needs to have a social responsibility to contribute to increasing the financial literacy of its employees. Employees who have good financial literacy will not only be more productive and prosperous but can also become agents of change in the surrounding environment, consisting of 7 employees and 11 members of the general public who took part in this service activity. The main aim of this activity is to provide an introduction and knowledge about the capital market in order to broaden understanding and improve financial literacy skills, especially in capital market investment, to employees and the general public. The method in this service is Focus Group Discussion as a way to increase financial literacy among employees. The results of this activity show that by increasing financial literacy among employees of PT. Infinity General Consulting provides an understanding of economic principles, financial systems and financial management which is expected to be able to optimize personal finances and contribute to the company's progress in creating a responsible financial culture in the work environment. The implications of this service provide information to the public about the importance of managing financial literacy in long-term investments and PT. Infinity General Consulting as the first-class trading consultant in West Nusa Tenggara.